Exploring critical factors influencing tourists’ perception in selection of destination: structural equation modelling approach on Bangladeshi market - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Rahman, Mahbubur (Institute of Management and Information Science, 2010)
The objectives of this research were to exploring critical factors influencing tourists' perception in selection of destination for travel in Bangladesh. The specific objectives of the study are: to identify and asses the factors that are influencing tourists in selecting destination; to find out the relationship between those factors and the consumers perception; to offer some recommendation for better marketing strategy to attract more tourists. In this study primary data had collected through distribution of questionnaires to the visitors on important tourists spot. Data from 180 completed questionnaires were analyzed quantitatively by variety of statistical techniques, including factor analysis and structural equation modeling to investigate the relationship among the variables. Three important factors like destination brand image, internet adoption, and customers' satisfaction are identified of the selection of destination by a traveler. The results of the structural equation modeling reflected that internet adoption and customers satisfaction played a significant role that are influencing tourist's perception in selection of destination for travelling. The survey was conducted only for one month's (December'09), which permitted only winter tourists to be surveyed. Thus, most of the respondents were winter tourists not representative of year round tourism. Only few dimensions were analyzed in this study, so further research can be done by using factors such as socio cultural, outdoor activities, Income, cultural distance with larger sample size. The overall conclusions and discussion of the findings should provide a framework for the practical planning and implementation of planning strategies in the tourism context.